(untitled) (Ameghiniana, 2014)
A jaw referred to Lama (Vicugna) aff. L. (V.) gracilis (Gervais and Ameghino) is described. It was found in loess beds of Upper Pleistocene age on the eastern slope of the Sierra Chica, Córdoba Province, Argentina. Taxonomic and paleoenvironmental aspects are discussed. The present altitude range of Lama (Vicugna) vicugna (Molina) is above 3700 m, but the Late Pleistocene record of Lama (Vicugna) aff. L. (V.) gracilis described here was found at 446 m, presumably reflecting similar steppe vegetation growing on loessic soils.